Design and Experiment of a Multi-mode Gripper - Zhao Chunhui; Wan Xiaojin (Jixie chuandong)
In this study, a generalized gripper with multiple modes is designed so that it can grasp various sheet parts. The gripper lies in two sets of fingers and two sets of compact force transmission mechanisms. Firstly, a kinematic model of the hybrid spatial multi-linkage mechanism of gripper is established by means of the D-H method. Multi-objective optimization is performed to maximize workspace, mechanical gain, and structural stiffness; three groups of gripper structure parameters are obtained to construct the virtual prototype; by comparing the results of the optimization process with those of the virtual prototype, the results indicate that the proposed optimization procedure can acquire a larger workspace and greater mechanical gain. Finally, according to the optimized parameters, a generalized gripper is manufactured. Three different grasping mode experiments are carried out to verify the feasibility of the gripper.